Urban theory of/from the Global South: a systematic review of issues, challenges, and pathways of decolonization - Chakrabarti, Debapriya (Frontiers in Sustainable Cities, 2023)
Urban Studies in recent decades have acknowledged that the cities of the Global South are epistemically, methodologically, and empirically different. However, the Southern cities theorisations continue to be considered outside mainstream urban theories. Also, there remains discrepancies and imbalance in the production of Southern cities scholarship. Not only are knowledge produced and published mostly in the West, but Southern scholars based in the Global South face increasing marginalisation due to politics of access, affordances, and production of knowledge. With growing discussions around the politics of visibility and institutional affiliations, this study aims to systematically map and analyse the dynamics and geography of knowledge production in the field. Through a scientometric review this paper firstly, unpacks the plethora of urban theory and related publications that theorises the Global South and places them according to where and by whom this was published. Secondly, this paper traces the need for urban theory and production of knowledge following the decolonisation agenda to be produced by and for the South. Finally, it closes with addressing the ways forward to progress urban theory and empirics from the South through production and coproduction of knowledge for and by the South.